Leadership patterns among public school principals and their relationship to the degree of improved job satisfaction from the point of view of teachers in Jordan - Alkailani, Nesreen Khaled (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the leadership patterns prevailing among the principals of public secondary schools in the University/ Capital Brigade of Amman and their relationship to improving the level of job satisfaction among employees. The link and resolution survey descriptive approach was used as a study tool, whose sincerity and stability were confirmed. The sample was made up of 323 employees and employees of the State High Schools Brigade of the University/ Capital Amman for the 2021/ 2020 academic year selected in a random class manner. The results showed the prevailing leadership patterns in the following descending order (democratic leadership, positional leadership, autocratic leadership, strategic leadership, lenient leadership) , job satisfaction may provide satisfaction with the style of leadership and supervision well and showed satisfaction with the working environment to a moderate degree, and a strong positive relationship of job satisfaction with democratic leadership, positional leadership and strategic leadership, while the relationship of job satisfaction with the autocratic and lenient leadership was a negative relationship In addition, there are no statistically significant differences at the function level (α≤0.05) due to the variable of scientific qualification, and there are statistically significant differences at the function level (α≤0.05) due to the gender and age variables, the most prominent recommendations were the implementation of training programs to raise the awareness of leaders in leadership patterns, inform school principals of successful global experiences in order to follow up on developments and apply what is appropriate to us to maximize the benefit of educational outcomes, and continue to issue moral incentives to teachers.